The importance of logo and tagline in business (case study: orang kampung's product) / Nurul Shaheera Abu Khair - Abu Khair, Nurul Shaheera (Faculty of Art and Design, 2013)
This whole process consists of finding the solution for Orang Kampung logo and tagline with rebranding the new logo for Orang Kampung company. The background research focuses on the level impact of new direction corporate identity to help Orang Kampung well known by using their logo, where theoretical study is conducted through literature, references and reviews on written materials such as journals, previous research reports, books, newspaper or via internet to have a better understanding of research topic. References also involve acts, plans and any secondary data that is related to the study. Early reviews are also conducted in this stage to identify problems. Any information obtained will be used as a reference to provide a form of observation. Objectives and Research Methodology: Researcher will state the research objective and approach towards the solution of corporate identity to rebranding the logo of Orang Kampung. Besides that, researcher will include the research methodology to find the problems. The method that will use in this research is online survey and interview session. Researcher will interview En. Radzi as an assistant manager of Orang Kampung Companyand the online survey will spread through the Facebook since many people have their Facebook account. Analysis and Findings: This chapter is to conduct analysis with the data and information that have been collected. This chapter is very crucial especially to reach the aim of the whole study as it may change the outcome of the research. Study also involves analyzing the feedbacks from the respondents. The questionnaire contains 14 questions. The platform used to spread this questionnaire is through Facebook. There are 14 singleselect questions. The questionnaire is both written in Malay language and English. The total amounts of respondents are 50 people with different backgrounds and lifestyles. Conclusion and Recommendation: Final chapter of methodology shows results after all the analysis is done. As a conclusion, it can be conclude that the standardization in using the logo and tagline is very important in company. So that, consumer will know the product belong to which company. This involves coming out with new concept or strategy implement on current condition. There will be some recommendation that will be explained for improvement of the case study. Logo is cognitively complex beyond its early steps, and quite difficult to leam without instructional guidance, even if students are intellectually engaged with that learning. As a designers, there are to arrive at interesting original solutions that also communicate exactly what the client requires, they have to start by being critical of the problem. The more interesting the problem, the more likely the solution will be interesting.